2009
DOI: 10.1177/2156759x0901200404
|View full text |Cite
|
Sign up to set email alerts
|

Informing Principals: The Impact of Different Types of Information on Principals’ Perceptions of Professional School Counselors

Abstract: The study in this article provided principals with different types of information about professional school counseling and examined the impact on their perceptions. Results demonstrated that information about the ASCA National Model® influenced principals’ perceptions of the amount of time counselors should allocate to delivery of the guidance curriculum, system support, and responsive services, as well as ratings of the importance of performing inappropriate tasks in meeting the education mission of the schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 7 publications
1
27
0
Order By: Relevance
“…Researchers have found that school counselors' self-efficacy is a predictor of comprehensive programming (Ernst et al, 2017;Mullen & Lambie, 2016;Scarborough & Culbreth, 2008). Also consistent with the literature (Borders & Drury, 1992;Cole, 1991;Fye et al, 2017;Leuwerke et al, 2009;Studer & Oberman, 2006;Walsh et al, 2007), we found that school counselors believed that lack of administrative support is often an obstacle to implementing the ASCA National Model. School counselors in our study also revealed that they perceive lack of support from teachers and parents to be a barrier to such implementation.…”
Section: Discussionsupporting
confidence: 90%
“…Researchers have found that school counselors' self-efficacy is a predictor of comprehensive programming (Ernst et al, 2017;Mullen & Lambie, 2016;Scarborough & Culbreth, 2008). Also consistent with the literature (Borders & Drury, 1992;Cole, 1991;Fye et al, 2017;Leuwerke et al, 2009;Studer & Oberman, 2006;Walsh et al, 2007), we found that school counselors believed that lack of administrative support is often an obstacle to implementing the ASCA National Model. School counselors in our study also revealed that they perceive lack of support from teachers and parents to be a barrier to such implementation.…”
Section: Discussionsupporting
confidence: 90%
“…The development of this relationship requires that principals and school counsellors have a shared understanding of the appropriate roles and activities that the counsellor should perform (Leuwerke et al 2009). …”
Section: Discussion Of the Resultsmentioning
confidence: 98%
“…Kör () found self‐leadership to have a full mediating role between perceptions of entrepreneurial orientation (an organization's position in being able to innovate combined with a willingness to innovate) and innovative work behaviors. School administrators/principals may not have been exposed to the ASCA National Model in their training programs (Dollarhide, Smith, & Lemberger, ; Leuwerke, Walker, & Shi, ) and, therefore, may hold an unclear understanding of school counselors' roles, duties, and leadership efforts. Given that school counselors are the means through which school administrators most often learn about the school counselor's role and comprehensive school counseling programs (Graham, Desmond, & Zinsser, ; Mason & Perera‐Diltz, ), having strong self‐leadership skills and an entrepreneurial orientation is advantageous to school counselors in advocating for their roles and implementing effective school counseling programs.…”
Section: Self‐leadershipmentioning
confidence: 99%